Core java. fundamentals - Horstmann, Cay S., 1959- (Prentice Hall, 2016)
As the leading no-nonsense tutorial and reliable reference, this book carefully explains the most important language and library features and shows how to build real-world applications with thoroughly tested examples. Core Java Volume I -- Fundamentals walks students through the all details and takes a deep dive into the most critical features of the language and core libraries. -- Provided by publisher.